Two-body B meson decays to η and η′: Observation of B → η′K - Behrens, B; Ford, W; Gritsan, A; Krieg, H; Roy, J; Smith, J; Zhao, M; Alexander, J; Baker, R; Bebek, C; Berger, B; Berkelman, K; et al. (1998)
In a sample of 6.6 × 106 produced B mesons we have observed decays B → η′K, with branching fractions B(B+ → η′K+) = (6.5-1.4+1.5 ± 0.9) × 10-5 and B(B0 → η′K0) = (4.7-2.0+2.7 ± 0.9) × 10-5. We have searched with comparable sensitivity for 17 related decays to final states containing an η or η′ meson accompanied by a single particle or low-lying resonance. Our upper limits for these constrain theoretical interpretations of the B → η′K signal.